MENUMBUHKAN BUDAYA MENABUNG SEJAK DINI: PROGRAM EDUKASI LITERASI KEUANGAN BAGI SISWA SEKOLAH DASAR - Puspita Sari; Trisna Trisna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Financial literacy education from an early age is a strategic step in shaping children’s character, discipline, and independence. This community service program was implemented at SDN Kabinuang with a focus on fostering a saving culture among elementary school students through simple, practical, and engaging approaches. The implementation methods included interactive material delivery, discussions, and hands-on saving practices using a class piggy bank managed collectively. Teachers played the role of facilitators who motivated students, while parents contributed by encouraging children to bring savings money every day. The results of the program indicated a significant improvement in students’ understanding and habits in managing pocket money. Most students were able to set aside a portion of their allowance for savings and demonstrated more controlled spending behavior. Moreover, the program instilled social values such as cooperation, solidarity, and mutual care among peers. Therefore, the saving program at an early age proved to be effective not only in building financial awareness but also in shaping positive character development beneficial for students’ future.